Assessment of Chitosan-Based Hydrogel and Photodynamic Inactivation against Propionibacterium acnes - Frade, Maria Lucia (Molecules, 2018)
Chitosan (CH) is a biopolymer that exhibits a number of interesting properties such as anti-inflammatory and antibacterial activity and is also a promising platform for the incorporation of photosensitizing agents. This study aimed to evaluate the efficacy of antimicrobial activity of chitosan hydrogel formulation alone and in combination with the methylene blue (MB) associated with antimicrobial photodynamic therapy (aPDT) against planktonic and biofilm phase of Propionibacterium acnes. Suspensions were sensitized with 12.5, 25.0, 37.5, 50.0 μg/mL of MB for 10 min and biofilms to 75, 100 and 150 μg/mL for 30 min then exposed to red light (660 nm) at 90 J/cm(2) and 150 J/cm(2) respectively. After treatments, survival fractions were calculated by counting the number of colony-forming units. The lethal effect of aPDT associated with CH hydrogel in planktonic phase was achieved with 12.5 µg/mL MB and 1.9 log(10) biofilm reduction using 75 µg/mL MB. Rheological studies showed that formulations exhibited pseudoplastic non-Newtonian behavior without thixotropy. Bioadhesion test evidenced that the formulations are highly adhesive to skin and the incorporation of MB did not influence the bioadhesive force of the formulations.